Research on timing method of prepayment meter based on edge computing - Li Jiangchao; Wang Wenqiang; Li Peng; Yuan Yanfang; Xue Binbin; Yang Kewen (Dianzi Jishu Yingyong, 2024)
With the construction of the power IoT and the increasing popularity of smart meters, solving the problem of abnormal clock of meters and correcting the clock deviation of meters has become an increasingly important task for power companies. For prepayment meters with clock deviations exceeding 5 minutes, the current common approach is to correct them through point-to-point cipher text timing. However, the increase in the number of such meters out of tolerance will put a significant burden on the central station's timing work. In response to this issue, drawing on the concept of edge computing, which involves splitting the overall task and allocating parts of it to edge nodes for distributed completion, this article proposes a batch electricity meter calibration method based on edge computing. The method utilizes techniques such as bulk task deployment from the central station and encryption by the edge nodes, enabling batch calibration of clocks with significant differences in electricity meters, reducing the operational pressure on the central station system and improving its efficiency.